2014
DOI: 10.1523/jneurosci.3615-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Temporal Integration in Autism Spectrum Disorders

Abstract: The new DSM-5 diagnostic criteria for autism spectrum disorders (ASDs) include sensory disturbances in addition to the well-established language, communication, and social deficits. One sensory disturbance seen in ASD is an impaired ability to integrate multisensory information into a unified percept. This may arise from an underlying impairment in which individuals with ASD have difficulty perceiving the temporal relationship between cross-modal inputs, an important cue for multisensory integration. Such impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

36
414
7
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 419 publications
(460 citation statements)
references
References 37 publications
36
414
7
3
Order By: Relevance
“…At another moment when salient auditory and visual cues were provided together (time point 3), TD subjects showed prominent communication across sensory modules, while it did not happen in the ASD case. This last observation is well in line with recent findings of atypical multisensory integration in ASD (Stevenson et al, 2014). Importantly, as those interplays across functional systems were present in both groups of subjects, with similar dynamics, in the setting of a similar reference group of healthy subjects (Supporting Information, Figure 7), one should interpret the absence of response as a greater heterogeneity in the way ASD subjects responded to the movie.…”
Section: Discussionsupporting
confidence: 92%
“…At another moment when salient auditory and visual cues were provided together (time point 3), TD subjects showed prominent communication across sensory modules, while it did not happen in the ASD case. This last observation is well in line with recent findings of atypical multisensory integration in ASD (Stevenson et al, 2014). Importantly, as those interplays across functional systems were present in both groups of subjects, with similar dynamics, in the setting of a similar reference group of healthy subjects (Supporting Information, Figure 7), one should interpret the absence of response as a greater heterogeneity in the way ASD subjects responded to the movie.…”
Section: Discussionsupporting
confidence: 92%
“…As sensory systems are exceptionally tractable experimental targets in human neuroscience research, exploring the interaction between oxytocin and neocortical function should be a highly informative research area in the near term. For example, some individuals with autism show atypical multisensory integration in psychophysical tasks like the flash-beep illusion (Foss-Feig et al, 2010;Stevenson et al, 2014), which involves combining visual and auditory cues into a single percept. Will intranasal delivery of oxytocin narrow the window of sensory integration in these individuals, but perhaps only at younger ages when neocortical OXTR levels are highest?…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Temporal binding windows allow multisensory information to be integrated even when there might be slight temporal asynchronies . In individuals with ASD, it appears that there might be an enlarged or expanded temporal binding window as compared to TD individuals (Baum et al 2015;Foss-Feig et al 2010;Kwakye et al 2011;Stevenson et al 2014a;Wallace and Stevenson 2014). This would mean that individuals with ASD would perceive asynchronous stimuli as simultaneous more so than TD individuals would.…”
mentioning
confidence: 99%
“…Whereas some of these studies demonstrated unique MSI alteration when socio-communicative stimuli were used (Bebko et al 2006;Mongillo et al 2008;Stevenson et al 2014a), others discovered a more general MSI impairment across both social and non-social tasks (de Boer-Schellekens et al 2013).…”
mentioning
confidence: 99%